How Does an Introverted Personality Affect Students' Writing Abilities? - Sahid, Suardi; Dasra, Mini Enggelina Papua Putri; Hasyim, Ruslan (Universitas Islam Ahmad Dahlan (UIAD), 2023)
Personality is considered as one of the internal factors that has an impact on students' ability to learn languages. This research explores the impact of personality type on their English writing abilities, with a focus on Introverts. The test aims for objectivity, clarity, and precision, with formal notes and adherence to conventional academic structures and grammatical rules. Qualitative descriptive were used in this research. The sample for this research was students of the Seventh Semester English Language Education Writing Class of 2022/2023 at the University of Papua. The instruments used to collect data were the MBTI (Myers-Briggs Type Indicator) Test and Interview. Researchers use purposive sampling where the sample to be interviewed must have a high percentage of introverts. To find out, researchers distributed the MBTI test link to 20 samples. Of the 20 samples who took the MBTI test, there were 9 samples who were classified as introverts. furthermore, from the 9 samples, the researcher chose 4 samples to be interviewed. The results of this research reveal that every student who has an introverted personality does not necessarily have good writing skills, but the habits of students who have an introverted personality such as reading non-fiction or fiction books and writing stories about everyday life can help the students to improve their writing skills